The efficacy of different types of intradialytic exercise for patients undergoing hemodialysis: a systematic review and network meta-analysis of randomized controlled trials - HaiQiang Jiang; Yu Wang; Jia Peng; Shuang Wu; Chuanfang Wu (BMC Nephrology)
Abstract Background Intradialytic exercise interventions improve dialysis efficacy; however, their comparative efficacy remains unclear, limiting evidence-based clinical practice. Objective To systematically review and compare the effects of different intradialytic exercises on dialysis adequacy in patients undergoing hemodialysis. Methods A systematic search was conducted in PubMed, EMBASE, Web of Science, and the Cochrane Library for randomized controlled trials evaluating the efficacy of intradialytic exercise on dialysis adequacy in patients undergoing hemodialysis. Studies published in the database from its inception to November 1, 2023, were included. Statistical analyses were performed using Stata 15.0. Results A total of 24 studies involving 786 patients were included in this analysis. The interventions comprised intradialytic aerobic exercise (IAE), intradialytic resistance exercise (IRE), combined intradialytic aerobic and resistance exercise (IAE + IRE), intradialytic respiratory muscle exercise (IRME), intradialytic electrical muscle stimulation (IEMS), and routine hemodialysis nursing (RHN). Among all pairwise comparisons, only IRME versus RHN showed a statistically significant difference (MD = 0.09, 95% CI: 0.03–0.16). No statistically significant differences were observed in any other pairwise comparisons, including those involving RHN and those between different exercise modalities. Nevertheless, IAE + IRE demonstrated the highest surface under the cumulative ranking curve (SUCRA) values for both the urea clearance index and reduction rate. Conclusion Current evidence is insufficient to conclude that any specific type of intradialytic exercise significantly improves dialysis adequacy. Nevertheless, SUCRA rankings indicate a potential benefit, with IAE + IRE demonstrating the highest probability of benefit. Given the limited statistical power, further high-quality studies are warranted to confirm these findings. The review protocol has been registered with PROSPERO(CRD42023484645). Clinical trial number Not applicable.